Transforming to a smart hospital system: Proposed application in the Medina Maternity and Children's Hospital. Issue 4 (7th November 2016) - Alharbe, Nawaf; Atkins, Anthony S.
Abstract : Purpose: Expert knowledge is an important organisational resource, and organisations need to retain the knowledge learned by experience, which can be shared as part of inter-professional learning. In a healthcare context, radio-frequency identification (RFID) and ZigBee technologies can be used together, to provide real-time information for decision support and to create a secure and reliable smart hospital management information system (SHMIS) that allows the dynamic control of objects and transforms operational processes, while minimising any potential risks to patients and staff. Currently, the RFID technology in Saudi Arabia is being solely used for the monitoring of newborn infants, and some difficulties have been encountered during the different stages of tagging and monitoring. The current system in Medina Maternity and Children's Hospital (MMCH) uses battery-powered active RFID tags, which are expensive and require routine maintenance. This study aims to discuss the way in which the MMCH in Medina, Saudi Arabia, could be transformed into an SHMIS. Design/methodology/approach: The extraordinary growth of RFID and ZigBee technologies has made it possible to identify, locate and track objects in various environments in real time. The RFID technology is a non-contact identification technology that is cheap and reliable but has limited range in the case of passive tags. ZigBee has greater range and lower power consumption, giving more precise location of the object's movements (0.6 m). Passive RFID when combined with ZigBee technology can be used to improve services provided by healthcare organisations through continuous data collection and supporting real-time decision-making, by applying expert knowledge of domain experts to data produced by communication from electronic and sensor technologies. Findings: A prototype object-tracking system using RFID and ZigBee was developed to support the knowledge transformation for knowledge reasoning for decision support (KRDS), and the outcome of this research was validated with domain experts in hospitals in Saudi Arabia. Two feasibility case studies were conducted at MMCH in Saudi Arabia, to evaluate the proposed system. A survey was also conducted to address the requirements at MMCH, and the researcher adopted a range of strategy techniques, including interviews and meetings with staff, and the setting up of communities of practise (CoPs) at the target hospital. Research limitations/implications: This paper has investigated the transformation process of an automatic healthcare tracking and monitoring systems for the purpose of developing a smart system in Saudi hospitals. For the scope of the project, the prototype implementation was restricted to a laboratory environment, to demonstrate the proposed proof of concept. The next phase will include conducting a scale up of the system, with implementation and testing done in a real hospital environment. Originality/value: This paper proposes a prototype application of an (SHMIS that allows the dynamic control of objects and transforms operational processes, while minimising any potential risks to patients and staff.